Hydrogen sensing properties of ZnO nanorods: Effects of annealing, temperature and electrode structure - Ozturk, Sadullah; Kilinc, Necmettin; Torun, Imren; Kosemen, Arif; Sahin, Yasin; Ozturk, Zafer Ziya (Pergamon-Elsevier Science Ltd, 2014)
In this study, the hydrogen (H-2) sensing properties of vertically aligned zinc oxide (ZnO) nanorods were investigated depending on annealing, Pd coating, temperature and electrode structure. ZnO nanorods were fabricated by using hydrothermal method on a glass substrate and an indium tin oxide (ITO) coated glass substrate. In order to determine the effects of annealing on the H2 sensor performance, the nanorods were heated at 500 C in dry air. H2 sensing measurements were done in the temperature range of 25-200 degrees C. It was found that, the sensor response of Pd coated ZnO nanorods were much higher than the uncoated nanorods due to the catalytic effect of Pd thin film. Moreover, the un-annealed samples showed better sensor response than the annealed samples due to the number of oxygen deficiency. In addition, the lateral electrode structure showed higher sensor response than the sandwich electrode structure. Copyright (c) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ZnO; Nanorods; Hydrothermal process; H-2 sensor; Gas sensor